COMMUNICATION ETHICS ON SOCIAL MEDIA: RE-EXAMINING THROUGH TAFSIR AL-MISHBAH - Akbar, Muhammad; Ridho, Abdul Rasyid; Salam, Sobihatun Nur Abdul; Al Amin, Hulaimi (Universitas Islam Negeri Mataram, 2025)
The tentative claim is that there has been a shift in communication ethics on social media towards the negative. Many people exhibit forms of communication that contain hate speech hoax news. This study explores communication ethics from the perspective of M. Quraish Shihab's tafsir al-Mishbah. This research uses library research with data collection method through documentation. The results show that in Islam, communication must pay attention to good morals or ethics according to Islamic teachings. M. Quraish Shihab's thinking through his interpretation shows relevance to the objectives in communication ethics in general, namely maintaining speech, courtesy, mutual respect and humanizing humans.